Caged compounds of hydrolysis-resistant analogues of cAMP and cGMP: synthesis and application to cyclic nucleotide-gated channels - Hagen, Volker; Frings, Stephan (Biochemistry, 1996)
Photolabile compounds which rapidly release cAMP or cGMP after photolysis are widely used for in situ studies of signaling pathways inside cells. We synthesized two novel caged compounds, 4,5-dimethoxy-2-nitrobenzyl 8-Br-cAMP (caged 8-Br-cAMP) and 4,5-dimethoxy-2-nitrobenzyl 8-Br-cGMP (caged 8-Br-cGMP), which respectively release the hydrolysis-resistant analogues 8-Br-cAMP and 8-Br-cGMP. Their usefulness for physiological studies was examined in a mammalian cell line expressing the cyclic nucleotide-gated (CNG) ion channel of bovine olfactory sensory neurons. The synthesis procedure resulted in diastereomeric mixtures which were chromatographically separated into the axial and equatorial isomers of caged 8-Br-cAMP and of caged 8-Br-cGMP. The axial isomers which have a higher solubility and better solvolytic stability than the equatorial forms were used for experiments with CNG channels. Flashes of UV light produced steps in the concentration of 8-Br-cGMP which activated currents through CNG channels. Con...